PENGARUH PUASA RAMADHAN TERHADAP INDEKS MASSA TUBUH PASIEN DIABETES MELITUS TIPE-2 - Julahir Hodmatua Siregar (Jurnal Penelitian Kesmasy, 2019)
Ramadan fastingis donefor one full month, must be done every Muslim Ummah including those suffering from chronic diseases such as Diabetes Mellitus, did not eat and drink during 13,5-14 hours. At the time off as ting that there will be changes such as: activity, diet, hours of work, activities at night as tarawih prayer and tadarus. Aim: odetermine the effect of Ramadan fasting on body mass indexin patients with type 2 diabetes mellitus. Methods: A prospective longitudinal study of the fasting month of Ramadan until the end of the fasting Ramdhan on 19 patients who had been diagnosed with type 2 diabetes at Adam Malik Hospital. The data collected by taking blood sample sat the beginning and end of the fasting of Ramadan fasting. Data were analyzed using paired T-test, wilcoxon. Results: Of the 19 patients with type 2 diabetes, as many as 13 respondents (68.4%) male sex with a mean age of 57.26 years. Statistical tests performed showed me significant value in BMI, Waist Circumference. Conclusion: There are significant value of BMI, Waist Circumference and blood fasting glucosain patients with type 2 diabetes before and after Ramadan fasting